2002
DOI: 10.1116/1.1467664
|View full text |Cite
|
Sign up to set email alerts
|

Debris reduction for copper and diamond-like carbon thin films produced by magnetically guided pulsed laser deposition

Abstract: Amorphous diamond-like carbon film prepared by pulsed laser deposition with application of pulsed negative bias voltage High intensity femtosecond laser deposition of diamond-like carbon thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The plasma reduces laser-surface coupling by absorbing and reflecting a significant part of ablating laser pulse if its duration is longer than the time of plasma formation. Because of this fundamental reason, reduction of the LPP shielding effect is among the major approaches for improvement of the laser-surface coupling for nanosecond pulses [5][6][7][8][9][10][11][12]. Steady magnetic field [8][9][10][11][12][13][14][15][16][17][18][19]21], ablation under vacuum conditions [7,20], and dc electric field [21,22] are employed to remove the LPP from a laser beam, to confine LPP to a smaller volume, or to lower plasma density.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma reduces laser-surface coupling by absorbing and reflecting a significant part of ablating laser pulse if its duration is longer than the time of plasma formation. Because of this fundamental reason, reduction of the LPP shielding effect is among the major approaches for improvement of the laser-surface coupling for nanosecond pulses [5][6][7][8][9][10][11][12]. Steady magnetic field [8][9][10][11][12][13][14][15][16][17][18][19]21], ablation under vacuum conditions [7,20], and dc electric field [21,22] are employed to remove the LPP from a laser beam, to confine LPP to a smaller volume, or to lower plasma density.…”
Section: Introductionmentioning
confidence: 99%
“…6 We report the controlling of laser-produced tin plasma using a moderate magnetic field of 0.64 T. The presence of a magnetic field ͑B͒ during the expansion of a laser-produced plasma may initiate several interesting physical phenomena which includes conversion of the plasma thermal energy into kinetic energy, plume confinement, ion acceleration, emission enhancement, plasma instabilities, etc. [8][9][10] Tsui et al 11 demonstrated the effectiveness of debris reduction using magnetically guided pulsed laser deposition. Time-of-flight emission spectroscopy is used to study the flight time and velocity of the singly ionized tin ͑Sn + ͒ and neutral tin ͑Sn͒ species at various spatial points in the plasma.…”
mentioning
confidence: 99%
“…Also it has been reported that droplet-free thin films can be fabricated with the use of a B-field in PLD (Tsui et al, 2002).…”
Section: Introductionmentioning
confidence: 99%